Enhancing Gifted Students' Creative Thinking Through Science Laboratory - Costu, Fatma (WILEY, 2024)
The aim of this study was to examine the impact of the Predict-Explain-Observe-Discuss-Explain (PEODE)-based laboratory on enhancing the verbal and figural creativity of gifted students. The quasi-experimental research design utilised a pre- and post-test approach with a non-equivalent control group, consisting of 60 sixth-grade gifted students. The participants were randomly assigned into two groups: the experimental group (EG; n = 30) and the control group (CG; n = 30). During the study, the control group underwent traditional laboratory tasks, whereas the experimental group participated in PEODE-based laboratory tasks. Both groups engaged in laboratory work for a total of 16 h. Data were collected using the Torrance Test of Creative Thinking (TTCT) scale, and statistical analysis methods were applied. The results revealed significant differences in favour of the EG regarding both verbal and figural creativity. These findings suggest that the PEODE-based laboratory approach can effectively enhance the creative abilities of gifted students.
Keywords: creative thinking; creativity; giftedness; Predict-Explain-Observe-Discuss-Explain (PEODE); science laboratory; TORRANCE TESTS; SCHOOL; EDUCATION; COOKBOOK; PROGRAM; SKILLS; TASKS; Education & Educational Research